Egress-enhancing mutation reveals the inefficiency of non-enveloped virus cell exit. - Valerie J Rodriguez-Irizarry; Robert W Maples; Julie K Pfeiffer (PLoS Biology, 2025)
Viruses encounter a range of selective pressures, but inefficiencies during replication can be masked. To uncover factors that limit viral replication, we used forward genetics to enrich for a murine norovirus (MNV) mutant with faster replication. We sequentially harvested the earliest progeny in cultured cells and identified a single amino acid change in the viral NS3 protein, K40R, that was sufficient to enhance replication speed. We found that the NS3-K40R virus induced earlier cell death and viral egress compared with wild-type virus. Mechanistically, NS3-K40R protein disrupted membranes more efficiently than wild-type NS3 protein, potentially contributing to increased mitochondrial dysfunction and cell death. Immunodeficient mice infected with NS3-K40R virus had increased titers, suggesting that increasing egress did not reduce fitness in vivo. Overall, by using a forward genetic approach, we identified a previously unknown inefficiency in norovirus egress and provide new insights into selective pressures that influence viral replication and evolution.